Estrategias resilientes adoptadas frente al cambio climático en el área urbana del cantón Quevedo - Murillo Vélez, Juliana Liceth (2018)
The impacts of natural and anthropogenic origin caused by human activities could in the future affect the subsistence of populations, especially in developing countries. The Second Social Communication on Climate Change, points out that the likely impacts for Ecuador are temperature change, increase in emissions of greenhouse gases, etc. In this regard, the present investigation focuses on the city of Quevedo, secondary information was taken to elaborate the governmental and the primary information was obtained through fieldwork in the taking of 348 surveys with a sample size stratified by 9 parishes with a total of 30547 families. The results are three aspects: a) the appreciation of resilient measures by citizens, highlighting that 94.29% and 65.71% of respondents consider that there are high levels of noise, and that it occurs due to lack of regulation or application thereof in the city respectively. Another highlight is that 85.71% and 54.29% of respondents indicate that solid waste discharges exist in sectors and lack is strategies for a solution respectively. However, there are good expectations on the part of the respondents, 84.29% and 90% of the respondents suggest that the use of renewable energies constitutes a future and that their implementation and evolution should be facilitated respectively, and this will also favor the fight against climate change as 57.14% 75.71% of respondents would be willing to save energy and pay for more products and services. b) is related to interviews with focal points in the last 5 years we identified that in risk management, recorded floods affecting 13.5% of the population and that have been evacuated to 44.2% in the rainy season . Finally, and c) within the strategies that we could adopt are: implement restoration projects, recovery in the most sensitive natural areas, promote green areas, and above all their conservation, this in coordination with regional measures